Effects of a hybrid teaching model (SEM + TGfU) and the model of personal and social responsibility on sportsmanship and enjoyment in 4° Secondary and 1° Baccalaureate students (Efectos de un modelo híbrido de enseñanza (MED + TGfU) y el modelo de respon - Álvaro Gómez Buendía; Bernardino Javier Sánchez-Alcaraz Martínez; María Isabel Cifo Izquierdo; Alberto Gómez Mármol (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The application of pedagogical models can have positive effects on sportsmanship and students’ enjoyment of Physical Education (PE) lessons. The aim of this study was to compare the influence on sportsmanship and fun of the application of, on the one hand, the combination of the Sports Education Model (SEM) and the Teaching Games for Understanding (TGfU) model and, on the other, the Personal and Social Responsibility Model (PSRM). The participants in this study were a total of 85 Spanish teenagers, 39 girls and 46 boys, studying Secondary Education. They completed the SSI questionnaires adapted to Physical Education (SSI-PE) to analyse their enjoyment, and the Multidimensional Sportsmanship Orientations Scale (MSOS) to analyse sportsmanship. Results showed significant differences in enjoyment when applying both the hybrid model (SEM+TGfU) and the PSRM model (p < .01). It is concluded that both interventions with the hybrid model and the PSRM generate positive effects on students’ enjoyment.